1982
DOI: 10.1055/s-2007-971370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Coumarins from Roots of Angelica dahurica on Actions of Adrenaline, ACTH and Insulin in Fat Cells

Abstract: Experiments were carried out on the effects of various coumarins on the actions of adrenaline, adrenocorticotropic hormone (ACTH) and insulin in fat cells isolated from rats. Furocoumarins such as oxypeucedanin hydrate, bergapten, xanthotoxin, imperatorin, phellopterin activated adrenaline-induced lipolysis. Furocoumarins such as oxypeucedanin hydrate, imperatorin and phellopterin also activated ACTH-induced lipolysis. On the other hand, furocoumarins such as byak-angelicin, neobyakangelicol and isopimpinellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…In Traditional Chinese Medicine, the roots of A. dahurica have been used to treat headache, rhinitis, cold and toothache amongst others. Furthermore, pharmacological studies have shown that it has antimicrobial (11), hepatoprotective (12), antioxidative (13) and cholinesterase inhibitory activities (14), and activates dendritic cells (15) and the actions of lipolytic hormones (16). Furthermore, it inhibits the production of prostaglandin E 2 (17) and nitric oxide (NO) (18,19), and reduces the release of histamine (20).…”
Section: Introductionmentioning
confidence: 99%
“…In Traditional Chinese Medicine, the roots of A. dahurica have been used to treat headache, rhinitis, cold and toothache amongst others. Furthermore, pharmacological studies have shown that it has antimicrobial (11), hepatoprotective (12), antioxidative (13) and cholinesterase inhibitory activities (14), and activates dendritic cells (15) and the actions of lipolytic hormones (16). Furthermore, it inhibits the production of prostaglandin E 2 (17) and nitric oxide (NO) (18,19), and reduces the release of histamine (20).…”
Section: Introductionmentioning
confidence: 99%
“…and an isotretronic acid derivative that imparts its characteristic odor to this drug, 2) and the effects of furanocoumarins isolated on the actions of adrenaline, adrenocorticotropic hormone (ACTH), insulin in fat cells isolated from rats, 3) histamine release in the mouse peritoneal cavity, 4) and human microsomal cytochrome P450 3A activity. 5) Continued investigation of the coumarin components resulted in the isolation of five new spirobifuranocoumarins, dahuribirins A-E (1-5) and two bifuranocoumarins, dahuribirins F and G (6, 7) by repeated chromatographic separation from this natural medicine.…”
mentioning
confidence: 99%
“…To calculate the administered dose, the contents of eight coumarins in radix Angelicae dahuricae extract solution were determined by external standard method using the same chromatography conditions as described above. The contents of the eight coumarins (1)(2)(3)(4)(5)(6)(7)(8) in the extract were 540, 117, 74, 224, 361, 1210, 1860, 1600 μg/mL, respectively.…”
Section: Preparation Of Radix Angelicae Dahuricae Extractmentioning
confidence: 98%
“…[3]. Pharmacological studies have demonstrated that they have shown a variety of biological effects, such as antioxidative activity [4], antihistamine [5], antibacterial action [6,7], spasmolysis [8], and treatment of chronic venous insufficiency [9].…”
Section: Introductionmentioning
confidence: 99%